2019
DOI: 10.1111/ctr.13656
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glycemic control after pancreas transplantation for Type 1 and Type 2 diabetic recipients at a high volume center

Abstract: Introduction:The number of pancreas transplants (PTX) in patients with Type 2 diabetes (T2DM) has increased in response to excellent outcomes in appropriately selected patients.Not all pancreas transplant centers share an enthusiasm for performing PTX for T2DM out of concern for increased complication rates. This study aims to clarify the characteristics of T2DM recipients with successful outcomes to clarify which candidates are more suitable for PTX as means of maximizing access to this highly effective thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…Our study also suggests that posttransplant glycemic control, in terms of fasting glucose and HbA1c, was comparable between T1D and T2D patients. However, consistent with Andacoglu et al, 21 at the end of 3 years, we found that BMI was significantly higher in T2D compared to T1D recipients. Our study was consistent with Hau et al 16 in finding a higher fasting C‐peptide in T2D compared to T1D recipients, though the differences did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study also suggests that posttransplant glycemic control, in terms of fasting glucose and HbA1c, was comparable between T1D and T2D patients. However, consistent with Andacoglu et al, 21 at the end of 3 years, we found that BMI was significantly higher in T2D compared to T1D recipients. Our study was consistent with Hau et al 16 in finding a higher fasting C‐peptide in T2D compared to T1D recipients, though the differences did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies, 16,20,21,35 our study showed that pancreas transplantation was able to sustain normal blood glucose and HbA1c for at least 3 years in T2D recipients. Our study also suggests that posttransplant glycemic control, in terms of fasting glucose and HbA1c, was comparable between T1D and T2D patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of elevated C-peptide alone should not preclude the consideration for pancreas transplant, as these recipients have been shown to have equivalent outcomes when appropriate selection criteria are applied. 8,10,11,30 Pretransplant obesity has been shown to predict higher rates of patient and graft survival regardless of diabetic type. 10,22,23,30 Patients who develop obesity after transplant are likely susceptible to these risks and thus every effort should be made to mitigate weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In these carefully selected recipients, pancreas graft and patient survival approaches requisite benchmarks. 4,5,8,9 Analysis of the Organ Procurment Transplant Network/ United Network for Organ Sharging (OPTN/UNOS) database comparing pancreas transplants in insulinopenic or type 2 diabetic recipients demonstrated no difference in patient or graft survival in carefully selected patients. 2,10,11 Furthermore, the Scientific Registry of Transplant Recipients database analysis showed that combined pancreas and kidney transplantation afforded better survival compared to kidney transplant alone in type 2 diabetes, but univariate analysis identify donor and recipient age (and not the pancreas graft) as imparting survival advantage.…”
Section: Introductionmentioning
confidence: 99%